Incidence and factors associated with postoperative delirium after primary total joint arthroplasty in older adults: a systematic review and meta-analysis - Ni, Yandong; Yang, Xu; Yang, Yuelai; Zhang, Huachun; Peng, Sheng (Frontiers in Medicine, 2025)
BackgroundThe proportion of older adults undergoing total joint arthroplasty (TJA) is increasing annually. Postoperative delirium (POD) is a common and serious complication among older adults after surgery. However, the incidence and factors associated with POD following primary TJA in this population remain unclear.ObjectiveThis study aimed to assess the incidence of delirium after primary TJA in older adults and to identify factors associated with POD through a meta-analytic approach.MethodsA systematic literature search was performed in PubMed, Embase, Web of Science, and the Cochrane Library for studies published from inception to June 2025. Observational studies reporting POD incidence following TJA, including total hip arthroplasty and total knee arthroplasty in older adults (aged ≥60 years), were included. Pooled incidence rates and factors associated with POD were estimated using a random-effects model.ResultsAfter applying the inclusion and exclusion criteria, 35 studies involving 29,311 older adults undergoing TJA were included. The pooled POD incidence was 13.6% (95% CI, 12.2–15.0%), with substantial heterogeneity across studies. Advanced age, sleep apnea, hypertension, diabetes mellitus, coronary artery disease, stroke, chronic obstructive pulmonary disease, renal disease, solid tumors, dementia, Parkinson’s disease, psychiatric disorders, ASA class III/IV, substance use history, and blood transfusion were associated with increased POD risk. Conversely, higher educational attainment was identified as a protective factor.ConclusionThis study systematically reported POD incidence among older adults undergoing TJA and identified factors associated with POD These findings provide evidence to optimize perioperative management and develop prevention strategies for POD in this population.Systematic review registrationThis study was registered in INPLASY platform (number: INPLASY202570015).